Psychometric properties of the Arabic version of the Fertility Quality of Life (FertiQoL) questionnaire tested on infertile couples in Jordan - Salwa Al Obeisat (17733762) (2023)
Background The Fertility Quality of Life (FertiQoL) questionnaire assesses the quality of life of people with fertility problems. The present study aimed to assess the psychometric properties of the Arabic version of the FertiQoL in infertile couples in Jordan. Methods This study used a cross-sectional design among 212 participants with infertility problems. An exploratory factor analysis (EFA) and a confirmatory factor analysis (CFA) were conducted to investigate the underlying structure of the novel Arabic version of the FertiQoL tool. Results The Cronbach’s alpha values for the FertiQoL core domain, the FertiQoL treatment domain, and the total FertiQoL scale were 0.93, 0.74, and 0.92, respectively. The EFA indicated a two-domain model, with the first factor having 24 items and measuring "Core QoL". The second factor has 10 items and measures "Treatment QoL" in the context of infertility. The EFA and the CFA supported a two-factor model whereby the two factors explained 48% of the shared covariance between the analyzed quality of life indicators. The indices of goodness-of-fit of the model showed acceptable fit as follows: the chi-squared test (χ2) = 7.943, the comparative fit index (CFI) = 0.999, the root mean square error of approximation (RMSEA) = 0.001, and the Tucker-Lewis index (TLI) = 0.989. Conclusion The study's findings demonstrated the reliability and validity of the Arabic version of the FertiQoL for assessing the quality of life of infertile couples or those in Jordan with no pregnancy or childlessness. Other Information Published in: BMC Women's Health License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1186/s12905-023-02437-6